These are really starting to frustrate me, still its the last question in my self teach book, but they never show u the friggin workings!
it says: assuming that a = e^lna (which I know is a true fact anyway) when a >0 Proove that
ln(a^n) = nlna
Now I know that alogb = logb^a. But is the above bit to throw me or what. I could proove it if I just said let b = lna^n. But the above has thrown me...again.
Any help much appreciated
I
2007-01-02
08:09:44
·
2 answers
·
asked by
John W
2
in
Science & Mathematics
➔ Mathematics